2000
DOI: 10.1016/s1359-6454(00)00063-x
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer spectroscopy study of MgAl2O4-matrix nanocomposite powders containing carbon nanotubes and iron-based nanoparticles

Abstract: ÐMaterials involved in the catalytic formation of carbon nanotubes are for the ®rst time systematically studied by MoÈ ssbauer spectroscopy between 11 K and room temperature. Mg 1Àx Fe x Al 2 O 4 x 0:1, 0.2, 0.3, 0.4) solid solutions are transformed into carbon nanotubes±Fe/Fe 3 C±MgAl 2 O 4 composite powders by reduction in a H 2 ±CH 4 gas mixture. The oxides are defective spinels of general formulae Mg 2 1Àx Fe 2 xÀ3a Fe 3 2a q a Al 3 2 O 2À 4: Ferromagnetic a-Fe, ferromagnetic Fe 3 C and a g-Fe form, the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 21 publications
8
47
3
Order By: Relevance
“…Four components were used in the fits of the spectra: one doublet, two sextets and one singlet. No significant differences in parameter values between the presently measured transmission data and those obtained earlier by Coquay et al [4]were observed. According to these authors, the doublet is attributable to Fe 2+ substituting for Mg 2+ in the spinel structure.…”
Section: Cnts-fe-mgal 2 O 4 Nanocomposite Powderssupporting
confidence: 46%
See 2 more Smart Citations
“…Four components were used in the fits of the spectra: one doublet, two sextets and one singlet. No significant differences in parameter values between the presently measured transmission data and those obtained earlier by Coquay et al [4]were observed. According to these authors, the doublet is attributable to Fe 2+ substituting for Mg 2+ in the spinel structure.…”
Section: Cnts-fe-mgal 2 O 4 Nanocomposite Powderssupporting
confidence: 46%
“…The synthesis of the CNTs-Fe-Al 2 O 3 and CNTs-Fe-MgAl 2 O 4 and their characterization by X-ray diffraction, transmission Mössbauer spectroscopy, transmission-and scanning electron microscopy are described in detail elsewhere [3,4]. Briefly, the CNTs-Fe-Al 2 O 3 nanocomposite powders were prepared by a catalytic chemical vapor deposition (CCVD) route involving the reduction of α-( Mössbauer spectra at room temperature were collected with a spectrometer operating in constant acceleration mode with triangular reference signal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the amount of Fe 2+ upon reduction of the Fe/MgO oxide powders and the evolution of the amount of Fe 2+ in the CNTsFe-MgO nanocomposite powders versus the urea ratio are consistent with the values of the MgO unit-cell parameters presented in Table 2 46 have indeed shown that a 1-h reduction in H 2 at 1300°C is necessary to reduce a Mg 0.9 Fe 0.1 O solid solution fully. Previous works 4,14 indicated that the Fe 3 C phase detected in the post-reduction analysis corresponds to particles on the surface of the matrix grains that are involved in the formation of the CNTs and the thick carbon nanofibers. The amount of Fe 3 C is high in Fe10U1R, decreases steeply to reach a minimum in Fe10U4R, and then increases in Fe10U8R, where it is similar to the amount in Fe10U1R (Figure 12b).…”
Section: Resultsmentioning
confidence: 94%
“…Formation of iron carbide phases during carbon SWNT growth has been discussed previously in the literature based on in situ TEM, Mössbauer spectra analysis, and magnetic properties. [30][31][32][33][34] Those studies concluded that the Fe-C alloy particles are possibly responsible for the nucleation and growth of the nanotubes. A detailed analysis of carbon nanotube formation mechanism using the Fe-C phase diagram was described in Ref.…”
Section: M/m S = Coth͑ H/k B T͒ − K B T/ H ͑2͒mentioning
confidence: 99%